If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(6x-3)=(5x-4)
We move all terms to the left:
7(6x-3)-((5x-4))=0
We multiply parentheses
42x-((5x-4))-21=0
We calculate terms in parentheses: -((5x-4)), so:We get rid of parentheses
(5x-4)
We get rid of parentheses
5x-4
Back to the equation:
-(5x-4)
42x-5x+4-21=0
We add all the numbers together, and all the variables
37x-17=0
We move all terms containing x to the left, all other terms to the right
37x=17
x=17/37
x=17/37
| 7n-8n+8=n+4 | | X/7+x/5=12 | | 5v+2v+2=-12 | | 1.2x+13-8.7x=50.5 | | 2/3(x+4)=1/3(x+12) | | 1÷3=20÷d | | 4/9d+1/9=2/3 | | 4x-3(×-2)=21 | | 1.2x+13-8.7=50.5 | | 6x2+11x=2 | | 4(x-3)=-16;-1 | | 2x=1-(2-x)^1/2 | | 400=2x+2(2/3x) | | 3m=2m+3 | | 7x+6(7x+27)=-181 | | -3x+1=3+2x | | -19+4x-23=-2 | | 3=7–2s | | j+9=15 | | -2(2x-6)=-4(2x-10) | | 5/7x=23/14 | | 5(5t+1)=25t-7 | | 2t-3+t=30 | | (x-3)/7=(x+5)/6 | | --4/7=-2f/3 | | 2^2x=64 | | 4+2p=10(3-5p-2) | | -2(4a-3)=30 | | v+27=10v | | 4x=-8x-28 | | 2x+1/3-x-1/2=5/6 | | 7(s+5)^2-27(s+5)=4 |